Peningkatan Keterampilan Pengolahan Pangan Sayuran Organik secara Online bagi Kelompok Rumah Sayur SKM (Suka Karya Makmur) di Desa Somongari, Kaligesing, Purworejo, Jawa Tengah - Nurul Putrie Utami; Hadi Sasongko; Zuchrotus Salamah; Purwanti Pratiwi Purbosari (AJAD : Jurnal Pengabdian kepada Masyarakat, 2022)
Somongari Village was an organic farming location. Perishable vegetables require special handling to increase shelf life. There was a need for training which is expected to increase the knowledge and skills of the member of Kelompok Rumah Sayur SKM (Suka Karya Makmur), increase the selling benefit, and the shelf life of organic vegetables products. The training activities were processing vegetables from agricultural products into bittermelon chips, eggplant chips, tomato sauce, and chili sauce. The training began with product processing through food processing videos demonstration and then practiced it independently. Evaluation of the results of this activity was carried out in writing, verbally, direct observation of the process, and evaluation of the food products made. The result of this training is an increase in knowledge of participants and from verbal interactions and direct observation, it could be seen that the training materials can be understood and can be practiced well by the trainees.